The interdependence of coaches' and athletes' perceptions and satisfaction with performance - Lorimer, R. (International Journal of Coaching Science, 2011)
This study investigated the interdependence of coaches' and athletes' perceptions of the athletes' performance and their association with coaches' and athletes' satisfaction with the athletes' performance. One-hundred coach-athlete dyads completed the performance subscale of the Athlete Satisfaction Questionnaire (Riemer & Chelladurai, 1998) and the performance subscale of the Elite Athlete Self-Description Questionnaire (Marsh, Hey, Johnson, & Perry, 1997). The results of a structural equation model analysis indicated a level of interdependence between the paired coach and athlete variables. There was a significant association between individual's own perceptions of performance and satisfaction with performance. Additionally, coaches' perceptions of performance were significantly associated with athletes' satisfaction with performance, whereas athletes' perceptions of performance were not associated with coaches' satisfaction with performance. These results are discussed based on issues they raise for theory and practice